The inverse of a function...

Thomas Arts <>
Tue Mar 9 09:03:38 CET 2004


No, this is not possible without interpreting either the
source or the binary.

If you know more about your function f, you might be
able to compute the inverse from the answer, but
since you have not sepcified that, I guess you don't
have this information.

/Thomas

---
Dr Thomas Arts 
     Program Manager 
     Software Engineering and Management 
IT-university in Gothenburg 
Box 8718, 402 75 Gothenburg, Sweden 
http://www.ituniv.se/

Tel +46 31 772 6031 
Fax +46 31 772 4899 


----- Original Message ----- 
From: "Corrado Santoro" <>
To: <>
Sent: Monday, March 08, 2004 5:06 PM
Subject: The inverse of a function...


> Hi Erlang gurus,
> I have a function like this:
> 
> f(caesar) -> ...;
> f(caius) -> ....;
> f(giulius) -> ....
> 
> I would like to have a function that, given the name 'f', returns the
> list [caesar, caius, giulius] (or similar).
> Is it possibile to do this (obviously without re-interpreting the source
> file)?
> 
> Thanx,
> 
> -Corrado
> 
> -- 
> ======================================================
> Eng. Corrado Santoro, Ph.D.
> 
> University of Catania - Engineering Faculty
> Department of Computer Science and
> Telecommunications Engineering
> Viale A. Doria, 6 - 95125 CATANIA (ITALY)
> 
> Tel: +39 095 7382364           Fax: +39 095 7382397
>      +39 095 7382365
>      +39 095 7382380
> 
> EMail: 
> Personal Home Page:
>             http://www.diit.unict.it/users/csanto
> 
> NUXI Home Page:
>             http://nuxi.iit.unict.it
> ======================================================
> 
> 
> 



More information about the erlang-questions mailing list